Estudos fenotípicos e moleculares sobre variabilidade genética, qualidade de grãos e tolerância ao estresse por ferro em arroz - Marini, Naciele (2013)
There is a constant need for studies aiming to increase yield and quality traits in rice, which have to consider abiotic stress tolerance and genetic variability. This work had as objective to characterize rice mutant families regarding rice iron stress tolerance and validate a technique based on retrotransposons with the goal of detecting genetic variability in rice. Also, to analyse gene expression of genes involved in starch synthesis in the rice grain. Therefore, nine mutant families were characterized for phenotypic traits and iron content in hydroponic conditions. Twenty genotypes were molecularly characterized with the REMAP technique and three cultivars were analysed the profiled for starch biosynthesis related gene expression by qRT-PCR. The results obtained demonstrate that the genotypes BR-IRGA 409 and BRS7-Taim characterized as sensitive presented a higher accumulation of Fe2+ in the shoots. The mutant families CGF-Z-M9-444CD, CGF-Z-M9-328 and CGF-Z-M9-243, were ranked in this study as tolerant. The genotype CGF-Z-M9-444CD was one of the mutants that accumulated less iron in the tissues under stress conditions, being also characterized as resistant in the phenotypic analysis. The variables root length, number of roots, iron, zinc and manganese, were altered in response to hydroponic culture growth with excess iron. In the gene expression study, it was possible to detect contrasting genotypes regarding amylose content presented differential expression for some of the analysed genes. Some of these genes have their expression levels altered at the beginning of starch biosynthesis, suggesting a higher contribution at the beginning of grain filling and other genes at the end of grain maturation. There is a tendency, mainly, for the cultivar BRS Firmeza, to increase the activity of studied genes 20 days after flowering with a decrease at 25 days after flowering and a new increase at 30 days after flowering, indicating an association between the activity of these genes and the stay-green character and the late starch accumulation in this genotype. Also, according with the studies performed, it was possible to measure the genetic variability in the rice germplasm used using the REMAP with a combination of low cost and simple protocols. Therefore, it is possible to discriminate genotypes at DNA level with the goal of predicting genetic distance and directed crosses between elite genotypes, thus exploiting population variability and transgressive segregants within breeding programs